Implementation of Building Information Modeling (BIM) Utilizing Tekla Structures for Work Volume Calculation (Institute of Technology Keling Kumang Project in Sekadau District) - Erliafina, Erliafina; Lusiana, Lusiana; Syahrudin, Syahrudin (Jurnal Teknik Sipil, 2024)
In the construction industry, planners use contract drawings and the Work Plan and Conditions (RKS) to determine the work to complete. The conventional approach in calculating the volume and quantity of work usually relies on Microsoft Excel as a calculation tool based on AutoCAD drawings. However, this method is considered inefficient and time-consuming, which can affect the quality of the resulting infrastructure. Building Information Modeling (BIM) is a solution to improve efficiency in planning and managing construction projects. In this research, Tekla Structures was chosen for its ability to generate project drawings, manage and monitor projects, amplify details with high accuracy, and automatically calculate the volume of work after modelling. This research aims to encourage wider application of digital technology in the construction industry in Indonesia. The results showed that comparing the total volume of concrete work between the calculation using Tekla Structures and secondary data had an accuracy rate of 87.61%, with a deviation of 12.39%. Meanwhile, the total volume of reinforcement works showed an accuracy of 95.66% with a deviation of 4.34%. This insignificant volume difference indicates that Tekla Structures can be relied upon to calculate the volume of work, especially in detailing and reinforcement. Although the accuracy of volume calculation is already high, improvement of the BIM model is still needed to make it closer to the actual conditions in the field. One of the efforts that can be made is to integrate real-time data from the field into the BIM model so that the accuracy of calculations increases and can support planning and project management more effectively.